2018
DOI: 10.1007/s13201-018-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of ligninolytic enzymes from novel Klebsiella pneumoniae strains and its application in wastewater treatment

Abstract: The presence of lignin and its derivatives in pulp effluent increases the pollution load on the environment. With an aim of better degradation and decolourization of wastewater, this study proposes the utilization of different ligninolytic enzymes from novel bacterial strains. Four novel bacterial strains of Klebsiella pneumoniae (K. pneumoniae strains NITW715076, NITW715076_1, NITW715076_2 and NITW715076_3) were isolated and identified. The ligninolytic enzymes were characterized by plate assay method. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 28 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…K. pneumoniae strain NX-1 isolated from leaf mold samples in China could efficiently produce lignin peroxidase and laccase [ 60 ]. Four strains of K. pneumoniae isolated from the pulp and paper industry in India were designated as manganese peroxidase and laccase producing bacterium [ 61 ]. It is evidenced that Klebsiella species represent a promising source of ligninolytic enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…K. pneumoniae strain NX-1 isolated from leaf mold samples in China could efficiently produce lignin peroxidase and laccase [ 60 ]. Four strains of K. pneumoniae isolated from the pulp and paper industry in India were designated as manganese peroxidase and laccase producing bacterium [ 61 ]. It is evidenced that Klebsiella species represent a promising source of ligninolytic enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Laccase purified from K. pneumoniae by using ABTS as substrate. The K m values were 0.467, 3.97 and 0.38mM for NITW715076, NITW715076_1 and NITW715076_2 K. pneumoniae strains, respectively [26] .…”
Section: Figure (4): Effect Of Different Temperatureson Laccase Stabilitymentioning
confidence: 95%
“…Genera Klebsiella and Escherichia both have been known to mineralize and utilize lignin and lignin related products as carbon source. Lab-scale expression studies of laccases and manganese peroxidase (MnP) have demonstrated the lignin degradation potency of both these genera in addition to their ability for utilizing lignin degradation intermediates vanillyl alcohol and syringaldehyde (Gaur et al 2018;Tian et al 2014). Zeng et al (2011) studied the extraction and over-expression of laccase CueO from E. coli JM109 strain responsible for degradation of benzo [a] pyrene.…”
Section: Microbial Community Compositionmentioning
confidence: 99%
“…Results of the current study supported the findings of earlier researchers wherein, the above enzymatic pathways were reported to be active in several bacterial genera belonging to different classes viz., α-Proteobacteria (Brucella, Rhizobium, Sphingobium, Sphingomonas), β-Proteobacteria (Burkholderia sp. ), γ-Proteobacteria (Pseudomonas, E. coli, K. pneumoniae) (Akita et al 2016;Bugg et al 2011;Gaur et al 2018;Pandit et al 2016;Prabhakaran et al 2015;Tian et al 2014;Zeng et al 2011). Researchers are increasingly targeting new sources like marshy sediments, rain and tropical forest soils, and grass lands for isolating more potent aromatic and lignolytic communities.…”
Section: Mining Of Lignin Depolymerizing Phylotypesmentioning
confidence: 99%